KEPUASAN MAHASISWA PENDIDIKAN EKONOMI TERHADAP PELAYANAN PERPUSTAKAAN DI FAKULTAS EKONOMI UNIVERSITAS NEGERI SEMARANG - Undari, Diyah; Ismiyati, Ismiyati (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The attributes of library services need to be analyzed in order to satisfy the students needs. The objective of this study were (1) to know the factors that determine Economics Educationâs student satisfaction and, (2) to know the most dominant factor in determining their satisfaction of the libraryâs services in Economics Faculty, Semarang State University.The data were collected by questionnaire, documentation and interview. Then the data were analyzed by factor analysis and descriptive percentage. The result ofthe factor analysis showed that the 28 analyzed variables were reduced to 23 variables. They were grouped into 8 new factors that determined student satisfaction was 62.668%. Meanwhile, 37.332% was influenced by other factors that are not defined in this model. (1) The convenience and the main products factor was17.971%, (2) the interaction factor was 8.878%, (3) the cleanliness factor was 7.830%, (4) the neatness factor was 6.731%, (5) the means of support factor was 6.348%, (6) the technical performance factor was 5.597%, (7) the building area factor was 4.918% and (8) the complementary product factor was 4.396%.